Virtual reality as a method of teaching Chinese - Shasaidova Lola Shamaksudovna (Genius Journals, 2021)
Modern innovative technologies play an important role in the educational process of higher educational institutions. To improve the Chinese language teaching system and improve the quality of teaching, it is necessary to introduce a variety of interactive teaching methods.The article explores a relatively new technology in education - virtual reality. The possibility of using VR technology in Chinese language lessons to create real conditions for communication and language use is considered.
Keywords: Chinese language; interactive methods; technologies